CD8+ T Cells in GCA and GPA: Bystanders or Active Contributors? - Reitsema, Rosanne D.; Boots, Annemieke M. H.; van der Geest, Kornelis S. M.; Sandovici, Maria; Heeringa, Peter; Brouwer, Elisabeth (Frontiers in Immunology, 2021)
Vasculitis refers to inflammation of blood vessels and can cause a variety of serious complications depending on which vessels are affected. Two different forms of vasculitis are Giant Cell Arteritis (GCA) and Granulomatosis with Polyangiitis (GPA). GCA is the most common form of vasculitis in adults affecting the large arteries and can lead to sight loss and development of aneurysms. GPA affects small- and medium-sized blood vessels predominantly in the lungs and kidneys resulting in organ failure. Both diseases can potentially be fatal. Although the pathogenesis of GCA and GPA are incompletely understood, a prominent role for CD4+ T cells has been implicated in both diseases. More recently, the role of CD8+ T cells has gained renewed interest. CD8+ T cells are important players in the adaptive immune response against intracellular microorganisms. After a general introduction on the different forms of vasculitis and their association with infections and CD8+ T cells, we review the current knowledge on CD8+ T-cell involvement in the immunopathogenesis of GCA and GPA focusing on phenotypic and functional features of circulating and lesional CD8+ T cells. Furthermore, we discuss to which extent aging is associated with CD8+ T-cell phenotype and function in GCA and GPA.